STRUCTURE OF GLASSES AND MELTS - Wilding M.C.; Benmore C.J. (My University, 2006)
Neutrons offer the opportunity to determine the structure of liquid and amorphous materials directly by diffraction. The total structure factor, S(Q), determined in the diffraction experiment is directly related to the real space pair distribution function of the liquid or glass by Fourier transform. Neutrons are in many ways ideal probes for liquid and amorphous materials, they are very penetrating and generally equally sensitive to light and heavy elements. It has however been the case that application of neutron diffraction to amorphous materials of interest to the geoscience community is limited because the samples of interest are chemically complex, large samples are required for neutron diffraction and in situ studies at pressures and temperatures pertinent to the earth's interior are not easily achievable. Nevertheless, there is an extensive literature devoted to studies of glass and liquids. Chemically complex liquids and glasses can be studied if the partial structure factors can be determined either by using isotopic substitution techniques, or more cheaply, by combining data from neutron and X-ray diffraction experiments. In oxide materials, the scattering of neutrons from oxygen in the sample may account for up to 60% of the scattered signal which means that in the real space transform, oxygen-related correlations can mask metal-metal correlations that reflect clustering and connectivity of coordination polyhedra, that potentially can be used to link amorphous structure with macroscopic properties. Combined neutron and high energy X-ray measurements can be used to identify different partial contributions to the PDF; this is particularly effective for the oxygen-bearing systems that dominate the interior of the Earth and other planets. The PDF is merely the starting point for interpreting amorphous structure, some form of model is invariably used to interpret the data and the quality of these models is judged on how well the short- and intermediate-range structure is reproduced in the S(Q) or G(r.) Developments in the specialized sample environments for use in combination with neutron diffraction mean that the change in liquid or glass structure with pressure and temperature can now be ascertained. Although few studies on the changes in amorphous structure with pressure have been made, they generally show large changes in both intermediate and short range order. The nature of these changes remains controversial with regard to polyamorphism and the high pressure liquid regime is as yet largely unexplored. Similarly, high temperature sample environments provide opportunities to examine the structure of metastable, supercooled liquids where most of the changes in liquid transport properties (i.e., viscosity) occur but in which a direct link between structure, rheology and structural relaxation has yet to be made. As sample environments become developed there are opportunities to probe extremes of temperature and pressure offered by the advent of new neutron sources and instruments. The Spallation Neutron Source (SNS) and new second target station at ISIS offer high neutron fluxes and there is the opportunity to examine small samples such as beads of levitated liquid, exotic glasses and samples in pressure cells. Instruments such as SNAP and NOMAD (SNS) are being commissioned (2008 and 2010 respectively) to examine disordered materials, SNAP is dedicated to examining materials under extremes of pressure, and new cells for high pressure experiments built, micro focusing and supermirror guides will result in better counting statistics and opportunities to examine liquid and amorphous materials at high pressure and temperature (Parise 2006, this volume). The NOMAD instrument will be dedicated to the study of atomic scale structure of liquids, glasses and disordered crystals. Following the philosophy of the SANDALS instrument at ISIS and high energy diffraction at 3rd generation synchrotron sources, the combination of high energies and low angles of scatter will be used to minimize the corrections and enable sophisticated sample environment apparatus to be used. Elliptical 3He tubes will increase detector efficiency of the higher energy neutrons and continuous angular coverage will be maintained. Focusing devices will be used for longer wavelength neutrons. The large increase in neutron intensity will therefore enable higher resolution, experiments on smaller samples and smaller contrast isotope substitution experiments than are currently feasible. Copyright © Mineralogical Society of America.